Conventional Control Strategies in Building Energy Management - Mahrouch Habiba; Haidi Touria; Derri Mounir; Hbiak Ishak; Mellouli El Mehdi; Mbarki Fatima Ezzahra (E3S Web of Conferences)
Building energy management is a critical component of global efforts to address climate change and environmental sustainability. Buildings account for a significant portion of worldwide energy consumption, making effective energy management in this sector crucial for reducing electricity costs and mitigating greenhouse gas emissions. This review article provides a comprehensive overview of conventional control methods used in building energy management, drawing from the latest research published in international journals and conferences. The review critically examines various control strategies, including hierarchical control. It highlights the key features, configurations, advantages, and limitations of these different approaches. The article also identifies the main challenges and research gaps in existing building energy control methods. These include the efficient control of complex, non-linear, and uncertain building systems. To address these issues, the review explores future research directions focused on developing adaptive, robust, and non-linear control techniques. The guidelines and control strategies discussed in this work aim to support the achievement of sustainable development goals through the optimization of energy management in buildings. By presenting the state-of-the-art in this field, the review provides valuable insights to researchers, building managers, and policymakers working towards a more energy-efficient and environmentally-sustainable built environment.